Potato Yield and Water Use Efficiency Responses to Irrigation in Semiarid Conditions. (1st November 2015) - Camargo, D. C.; Montoya, F.; Ortega, J. F.; Córcoles, J. I.
Abstract : Potato ( Solanum tuberosum L.) yield is sensitive to water stress in the semiarid regions of Spain. This study was conducted to determine the effect of four irrigation treatments on potato tuber yield under one‐quarter (4.9 ha) of the total irrigation area (18.4 ha) of a center pivot system in Albacete, Spain, during 2011 and 2012. Four irrigation treatments were applied, representing 60, 80, 100, and 120% of potato crop water requirement (CWR). In 2011, crop yield differed between the 60% irrigation treatment and the other treatments, whereas in 2012, yield differed between irrigation treatments with high (100 and 120%) and low (60 and 80%) water supply. Water use efficiency (WUE) ranged from 8.6 to 11.6 kg m −3 in 2011 and 7.1 to 8.4 kg m −3 in 2012, with significant differences among treatments in 2011. Differences in harvest index (HI) were observed between the irrigation seasons due to weather conditions of the second year. The 80% treatment was more efficient or equally efficient compared with the unstressed treatments and therefore represents a viable option when there are limited water supplies or high water costs.